PENINGKATAN KEMAMPUAN MENULIS MELALUI MODEL PEBELAJARAN KONSTRUKTIVISME PADA MATA PELAJARAN BAHASA INDONESIA - Tinor Resdika Tampubolon (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This research was conducted on VIII graders of SMP Negeri 1 Tarutung in the 2016/2017 academic year consisting of 31 students who aimed to find out improving student learning outcomes writing travel reports through constructivism learning at Tarutung 1 Junior High School. Data collection instruments were carried out using tests of student learning outcomes, and observations. Data Analysis Techniques in this Classroom Action Research calculate the percentage of Classical Students Completeness in Learning, and calculate the percentage of Observation Results (Observation) of Teachers and Students. The results of this study were obtained that: in the first cycle completeness was obtained as much as 38.70%, while in the second cycle learning completeness was obtained as much as 87.09%. From direct observations made during the Learning Process (PBM) all learning groups appear to be involved in PBM. They appear responsive and enthusiastic about accepting and treating the learning sheets that the author has prepared beforehand. In short, the two cycles that have been carried out in PTK have been able to increase the activity and cohesiveness of learning. There is a change in learning behavior that is more positive than the previous habits with conventional learning patterns. Thus this CAR was carried out both cycles (after analyzing the results and the process) has shown an increase in writing learning outcomes for students of class VIII / 1 in SMP Negeri 1 Tarutung. Keywords: writing, travel reports, constructivism  Abstrak: Penelitan ini dilakukan pada siswa kelas VIII SMP Negeri 1 Tarutung tahun pelajaran 2016/2017 yang terdiri dari 31 orang siswa yang bertujuan untuk mengetahui peningkatan hasil belajar siswa menulis laporan perjalanan melalui pembelajaran kontruktivisme di SMP Negeri 1 Tarutung. Instrumen pengumpulan data dilakukan dengan menggunakan tes hasil belajar siswa, dan hasil pengamatan (observasi). Teknik analisis data pada Penelitian Tindakan Kelas ini menghitung persentasi ketuntasan belajar siswa secara klasikal, dan menghitung persentasi hasil pengamatan (observasi) terhadap Guru dan Siswa. Hasil penelitian diperoleh bahwa pada siklus I ketuntasan diperoleh sebanyak 38,70%, sedangkan pada siklus II ketuntasan belajar diperoleh sebanyak 87,09%. Dari pengamatan langsung yang dilakukan saat Proses Pembelajaran (PBM) semua kelompok belajar tampak terlibat dalam PBM.Mereka tampak responsif dan antusias menerima dan memperlakukan lembar-lembar pembelajaran yang telah penulis siapkan sebelumnya. Pendeknya kedua siklus yang telah dilakukan dalam PTK ini telah dapat meningkatkan keaktifan dan kekompakan belajar. Terjadi perubahan perilaku belajar yang lebih positif dari pada kebiasaan sebelumnya dengan pola pembelajaran konvensional. Kata kunci:  menulis, laporan perjalanan, konstruktivisme